Eksplorasi Ruang Kreativitas: Produk 'Smooth Bowl' UMKM Pejuang Rasa - Nanda Unzilatur Rochmah; Ni Made Ida Pratiwi (BADAN PENERBIT STIEPARI PRESS, 2023)
Along with the growing awareness of the importance of health and the adoption of a healthy lifestyle, UMKM Pejuang Rasa responds to this challenge by developing product innovations, one of which is the smoothie bowl product. The product innovation process, accompanied by internship implementation, involves a series of methods, including interviews, problem analysis, production planning, actual production, packaging, and product promotion. The Smoothie Bowl, a processed fruit product that has been frozen and topped with seeds and fruit slices, is packaged in a brown craft paper cup that can hold 360ml of smoothie. Introducing this product to the public is done consistently by implementing a promotion strategy supported by product photos. Through the conducted assistance, it is hoped that UMKM Pejuang Rasa can continue to grow by adapting and enhancing innovation.